2016
DOI: 10.3855/jidc.6876
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of coxsackievirus A16 associated with hand, foot, and mouth disease in Nanjing, China

Abstract: Introduction: Coxsackievirus A16 (CVA16) is a main pathogen in hand, foot, and mouth disease (HFMD) worldwide. This study intended to clarify the genetic characteristics of CVA16 associated with HFMD in a defined area in Nanjing, China. Methodology: A total of 175 CVA16 strains isolated from throat swabs between 2011 and 2013 were obtained through sentinel hospitals in Nanjing. Multiplex polymerase chain reaction (PCR) was used to amplify the VP1 sequence of local CVA16 strains, and their genetic relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Furthermore, sub-genogroups B1a and B1b associated with outbreaks of HFMD in Nanjing, Fujian, and Yantai, were recognised as the predominant subtypes circulating around the mainland [39,[53][54][55], which was consistent with the results of the present study in Guangzhou. The CVA-16 phylogenetic dendrogram indicated that sub- genogroup B1b, including 19 Guangzhou CVA-16, was dominant in our study, similar to the results of previous reports on other regions [53,55]. The Guangzhou CVA-16 located in the B1b group showed high similarity to the strain isolated in Shenzhen, a city adjacent to the Guangdong province.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, sub-genogroups B1a and B1b associated with outbreaks of HFMD in Nanjing, Fujian, and Yantai, were recognised as the predominant subtypes circulating around the mainland [39,[53][54][55], which was consistent with the results of the present study in Guangzhou. The CVA-16 phylogenetic dendrogram indicated that sub- genogroup B1b, including 19 Guangzhou CVA-16, was dominant in our study, similar to the results of previous reports on other regions [53,55]. The Guangzhou CVA-16 located in the B1b group showed high similarity to the strain isolated in Shenzhen, a city adjacent to the Guangdong province.…”
Section: Discussionsupporting
confidence: 92%
“…Intriguingly, one sequence was located in the sub-genogroup B1c, which has been reported only in Malaysia, France, and India [16,54]. Hence, we believed that one located in B1c was obtained from other countries via import transmission [55]. Comprehensive and long-term surveillance of HFMD is critical for understanding the trend of the epidemic and emergence of new genotypes, and for controlling EV infection in the future.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, B1b strains were spread more widely. [21][22][23][24] Thus, B1a and B1b subgroups of CV-A16 could be co-circulated in mainland China including Yunnan. Recombination is a general phenomenon for enteroviruses.…”
Section: Discussionmentioning
confidence: 97%
“…At present, phylogenetic analysis of CV‐A16 isolated from other provinces in China showed these strains belonged to subgroups B1a and B1b. Moreover, B1b strains were spread more widely . Thus, B1a and B1b subgroups of CV‐A16 could be co‐circulated in mainland China including Yunnan.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis of viral protein 1 gene sequences revealed that the EV-A71 genotype circulating in China since 2008 has been C4 ( 38 42 ); hence, the monovalent EV-A71 vaccines licensed in China were designed to target the C4 genotype. B1 has been reported to be the predominant genotype of CV-A16 circulating in China ( 40 43 ). Therefore, we reasonably conclude that in our cohort HFMD recurrences involving reinfections with enteroviruses of the same serotype were also highly likely reinfections with the same genotype.…”
Section: Discussionmentioning
confidence: 99%